Ethical stress in interpreting and translation: A literature review - Kalishchuk, Diana (East European Journal of Psycholinguistics, 2023)
Ethical stress is occupational stress resulting from disparities between one’s ethical values and expected behaviours that can lead to dreadful consequences for individuals and even burnout. This review focuses on studies of ethical stress in translation and interpreting; individual and situational factors that may lead to ethical stress; its moral, emotional, psychological, and professional implications. The literature review is based on the search of articles in peer-reviewed journals published in the 21st century. This study has found that ethical stress in translation and interpreting occurs when the job requirements do not match the capabilities, resources, needs or values of the translator/interpreter due to linguistic demand factors and non-linguistic ones, including environmental, interpersonal, and intrapersonal demands. Taken together, the obtained results suggest that (a combination of) various individual and situational factors (working conditions primarily) may trigger moral distress, emotional exhaustion, vicarious trauma, burnout, and, eventually, ethical stress. However, the correlation between individual and situational factors and the level of their impact on translators/interpreters have not been sufficiently studied. Moreover, very little research has been carried out into psychological consequences for the translators/interpreters caused by socio-ethical dilemmas they face. Recent studies confirmed the positive relation between (the level of) ethical stress and job satisfaction and performance. Still, little is known about the correlation between (relative) autonomy to make decisions and judgments and the level of ethical stress and impact on performance. Thus, further research into the ethical stress of translators/interpreters under natural working conditions rather than in laboratory and agency settings and its implication on their performance and general well-being is essential.Author: Diana Kalishchuk,   0000-0003-1952-5176  diana_kalishchuk@vnu.edu.ua